2002
DOI: 10.1093/jn/132.12.3704
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fiber-Rich Barley Products Beneficially Affect the Intestinal Tract of Rats

Abstract: The objective of this study was to investigate the effects of barley-rich diets in the intestinal tract of rats. Four test groups (A-D) of 10 young male Wistar rats were fed diets containing 50 g/100 g barley extrudates (A, B and D) or mixtures (C) for 6 wk; the control diet contained no barley. The barley-containing supplements in the test diets were: A = cultivar "HiAmi"; B = "HiAmi" and "Prowashonupana" (50:50); C = "Prowashonupana" and Novelose (50:50); D = "Prowashonupana" and amylose from maize (60:40). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 40 publications
2
82
0
Order By: Relevance
“…It is known that cereals, mushrooms and yeast facilitate bowel motility and can be used in amelioration of intestinal problems, particularly obstipation (Battilana et al, 2001;Dongowski et al, 2002). Nondigestible β-glucans, forming a remarkable portion of these materials, are also able to modulate mucosal immunity of the intestinal tract (Tsukada et al, 2003).…”
Section: Most Published Studies Described Effects Of Injected β-Glucamentioning
confidence: 99%
“…It is known that cereals, mushrooms and yeast facilitate bowel motility and can be used in amelioration of intestinal problems, particularly obstipation (Battilana et al, 2001;Dongowski et al, 2002). Nondigestible β-glucans, forming a remarkable portion of these materials, are also able to modulate mucosal immunity of the intestinal tract (Tsukada et al, 2003).…”
Section: Most Published Studies Described Effects Of Injected β-Glucamentioning
confidence: 99%
“…Accordingly, fermentable carbohydrates such as different types of resistant starch, non-starch polysaccharides (NSP) and nondigestible oligosaccharides have been shown to enhance proliferation of beneficial bacteria in the small intestine (Bikker et al, 2007). As a result, there was an increased production of straight-chain short-chain fatty acids (SCFA) that may be used as energy source by the host (Gaskins, 2001), but which are also known to exert selective antimicrobial effects against certain pathogens (Dongowski et al, 2002). On the other hand, excessive fermentation of dietary protein should be avoided because of the production of detrimental substances, including ammonia, amines and phenols (Jensen, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In a complex study (Dongowski et al 2002), the physiological effects of DF-rich barley-containing diets (particularly extrudates) from the wholegrain type were evaluated in male Wistar rats. The diets that were fed differed in their concentrations of total DF and of individual DF (for example, b-glucan, RS).…”
mentioning
confidence: 99%
“…The aim of that study was to investigate if barley-rich diets with an optimised DF composition would cause beneficial direct or indirect physiological effects in the intestinal tract. It was shown that feeding rats the diets containing 50 g barley products/100 g for 6 weeks resulted in increased masses of the caecum and colon as well as in higher weights of the intestinal contents, and in greater amounts of excreted steroids compared with those rats fed with the barley-free control diet (Dongowski et al 2002). There are only a few reports on the amount of steroids found in the intestinal tract during the feeding of barley-containing diets (Gallaher et al 1992;Lia et al 1995).…”
mentioning
confidence: 99%